Hubungan antara Pengalaman Pasien dengan Pemahaman Inform Consent Pada Pasien Operasi di RS Sarkies Aisyiyah Kudus - Faiq, Diana Luthfiana; Purnomo, Muhammad; Khairunnisa, Zunia (Innovative: Journal Of Social Science Research, 2025)
Informed consent is a vital communication process in healthcare that ensures patients understand information and make conscious medical decisions. This study aims to examine the relationship between patient experience and understanding of informed consent among surgical patients at RS Sarkies Aisyiyah Kudus. Using a quantitative approach and descriptive correlational design, 89 patients were selected through purposive sampling from a population of 114. Data were collected via observation, questionnaires, and documentation. Data were analyzed using univariate and bivariate analysis (Spearman Rho test). The results showed a positive and significant relationship between patient experience and informed consent understanding (r = 0.414; p = 0.000). Better patient experience was associated with higher understanding. Healthcare providers are advised to improve communication and information delivery, especially for patients with limited experience.